Bacteriuria with Unusual Uropathogens in Diabetics in Thi-Qar Province - Beden, Murtada W.; Mousa, Hind M (University of Thi-Qar Journal of Science, 2022)
This study was designed to investigate the causative agents of recurrent urinary tract infection in diabetic patients in Thi-Qar Province . The study included 87 Iraqi participants of whom 46 diabetics and 41 non diabetics healthy control . Urine samples were collected from each participant and cultured on blood and MacConkey agars ,followed by macro and microscopic identification and biochemical tests. API 20E and Vitek 2 compact systems were used as a confirmatory tests . The findings showed ,of the total 87 participants 60(69%) gave a positive growth for urine culture. The results also showed thatT2DM patients were more susceptible to UTI with positive urine growth of 23/26 (88%) compared to T1DM patients who showed 14/20 (70%), and the majority of cases were female. Escherichia coli is the most common isolates accounting for the majority of cases 29 (48%), followed by Klebsiellapneumoniae9(15%) and Acinetobacter radioresistens 8(13.3%).It can be concluded that diabetic patients are more susceptible to UTI, especially T2DM. According to the present results, the immune disturbance due to diabetic patients is taking tall on T2DM patients even with asymptomatic bacteriuria.